Analisis Pengaruh Mentoring Functions dan Organizational Socialization Terhadap Role Stress, Burnout, dan Turnover Intention Pada Generasi Y di Rumah Sakit di Jabodetabek - Karina Rizkatiar; Aryana Satrya (Program Studi Magister Manajemen FE Unsri, 2016)
This research aims to investigate factors that could determine Generation Y’s role stress and turnover intention, which are mentoring function and organizational socialization. Besides, this research also aims to analyze the effect of Generation Y’s role stress on turnover intention with burnout as a mediator. To investigate this, 260 nurses and midwives at hospitals in Bekasi, Depok, Kemayoran, and Kelapa Gading were surveyed. Data analysis is conducted using structural equation modelling. The result of this research showed that mentoring function is not negatively significant to role stress but it affects negatively to Generation Y nurses and midwives’s turnover intention. Besides, organizational socialization was also found negatively significant to role stress, while role stress that experienced of Generation Y will negatively affects turnover intention with burnout as a mediator. Thus, role stress of Generation Y at hospitals in Jabodetabek could be reduced by organizational socialization, and their turnover intention could be minimalized with mentoring function